2021
DOI: 10.5144/0256-4947.2021.232
|View full text |Cite
|
Sign up to set email alerts
|

Taurodontism in maxillary and mandibular molars using cone beam computed tomography in a dental center in Saudi Arabia

Abstract: BACKGROUND: Taurodontism is a dental anomaly characterized by altered crown root ratio that is often diagnosed by radiographic evaluation. A three-dimensional cone beam computed tomography (CBCT) can aid in the diagnosis and treatment of taurodontic teeth. Only one study has reported the prevalence of taurodontism in a Saudi population. OBJECTIVE: Determine prevalence and other characteristics of taurodontism in permanent maxillary and mandibular molars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
2
2
0
1
Order By: Relevance
“…The severity of this anomaly did not significantly vary across contemporary or historical periods, consistent with other findings [ 18 , 21 ]. The gene responsible for taurodontism, linked to X chromosome aneuploidy, may contribute to differences in severity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The severity of this anomaly did not significantly vary across contemporary or historical periods, consistent with other findings [ 18 , 21 ]. The gene responsible for taurodontism, linked to X chromosome aneuploidy, may contribute to differences in severity.…”
Section: Discussionsupporting
confidence: 91%
“…Both contemporary and historical populations, as described in this research, have consistently reported a higher prevalence of taurodontism in maxillary molars compared to their mandibular counterparts, a finding echoed by other scholars [ 4 , 8 , 11 , 18 , 21 ]. Interestingly, a study in the Turkish population suggested a greater prevalence of taurodontism in mandibular molars [ 19 ].…”
Section: Discussionsupporting
confidence: 70%
“…Jabali AH et al found prevalence of taurodonts to be 0.1 % in Saudi Arabia. 18 These values are considerably low as compared to other studies. The reason can be attributed to differences in ethnicity, diagnostic criteria differences and differences in specific teeth.…”
Section: Discussionmentioning
confidence: 60%
“…The diagnosis of taurodontism is usually a random finding, made through routine two-dimensional (2D) radiographic imaging such as periapical or orthopantomography, but these techniques may not be adequate to accurately classify the condition due to possible distortion, leading in turn to inaccurate measurements. 17 In our study, cone beam computed tomography (CBCT) imaging was considered to be appropriate for proper diagnosis and preparation for surgical extractions, to evaluate the proximity of the teeth to anatomical structures such as the inferior alveolar nerve, to evaluate the remaining lingual bone next to the lower right para-premolar and its proximity in the bucco-lingual dimensions to teeth No. 44 and 45.…”
Section: Discussionmentioning
confidence: 99%